Does Trauma Shape Identity? Exploring the Links Between Lifetime Trauma Exposure and Identity Status in Emerging Adulthood - Truskauskaite-Kuneviciene, Inga; Brailovskaia, Julia; Kamite, Yuka; Petrauskaite, Gabija; Margraf, Jürgen; Kazlauskas, Evaldas (Frontiers in Psychology, 2020)
In emerging adulthood, coherent identity plays a protective role against the development of the disturbed psychosocial functioning and is seen as one of the defining characteristics of positive youth development. The factors that shape the identity are still understudied and little quantitative research has addressed, how trauma exposure is linked with emerging adults’ identity. Therefore, the current study aimed to investigate how exposure to traumatic experiences over the lifetime is associated with current identity status among emerging adults in an academic environment and to explore links between different types of traumatic experiences as well as the severity of exposure to trauma and identity statuses. The study sample consisted of 1614 first- year undergraduate students from Lithuania with the age range of 18 to 29 years (M = 19.09, SD = 1.05, 68.28% female). The three distinct identity profiles were identified using the Latent Class Analysis, representing diffused, undifferentiated, and coherent identity statuses. The results provided no clear evidence of links between traumatic experiences and identity status for overall exposure and most types of traumatic events. However, our study concerns the potential importance of severe traumatic experiences, such as sexual trauma, on identity.